Aerial Views: Main Campus: Agricultural Engineering, circa 1955 (1955)
Caption reads: 'The agricultural engineering shop building in the foreground includes well equipped shops for farm mechanics, farm machinery hydrology, farm power, and rural electricity. Building at right provides drafting rooms, offices, and classrooms. Machine and welding shops are in the rear.' The aerial view is looking northeast at the Agricultural Engineering and NYA shops.